PENERAPAN, PELATIHAN DAN PENDAMPINGAN PEMANFAATAN SISTEM LAYANAN ADUAN MASYARAKAT DI TINGKAT KELURAHAN BERBASIS CLOUD APPLICATION DI KELURAHAN SOMAGEDE - Adam Prayogo Kuncoro; Tarwoto Tarwoto; Geza Andika Basten (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2018)
Modern information systems can be used to optimize and streamline business processes that exist in a company or organization. By using a well-designed information system, many benefits can be obtained by a company or organization. The information system began to be applied to the community line, and has even been widely used as a media link between the regional government to the central government and the related community. This service is an application of the information system design that was previously made by the proposal team, used as a media complaint by the community to the government department in the Somagede Village area, Banyumas Regency, which utilized the basis of a website application or known as cloud application, which was more effective and efficient compared to conventional community based complaints systems using paper format. The community can provide criticisms, suggestions, or information about the environment surrounding the officials of the Village of Somagede using an internet connection so they can access this complaint information system. This information system is designed to make it easier for Somagede District officials to process aspirations and complaints from the community.